2014
DOI: 10.1007/978-3-319-10404-1_63
|View full text |Cite
|
Sign up to set email alerts
|

Towards Personalized Interventional SPECT-CT Imaging

Abstract: The development of modern robotics and compact imaging detectors allows the transfer of diagnostic imaging modalities to the operating room, supporting surgeons to perform faster and safer procedures. An intervention that currently suffers from a lack of interventional imaging is radioembolization, a treatment for hepatic carcinoma. Currently, this procedure requires moving the patient from an angiography suite for preliminary catheterization and injection to a whole-body SPECT/CT for leakage detection, necess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…A more elaborate option is acquisition optimization schemata, where, for example, the robot adjusts the scanning speed to provide a simultaneously good spatial coverage and good detection statistics, generating patientspecific scans. Robotic nuclear imaging systems could find their application in real-time imaging of the radioactivity distribution during radioembolization of the liver, 13 or the application of radioguidance to laparoscopic surgeries. 31…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A more elaborate option is acquisition optimization schemata, where, for example, the robot adjusts the scanning speed to provide a simultaneously good spatial coverage and good detection statistics, generating patientspecific scans. Robotic nuclear imaging systems could find their application in real-time imaging of the radioactivity distribution during radioembolization of the liver, 13 or the application of radioguidance to laparoscopic surgeries. 31…”
Section: Discussionmentioning
confidence: 99%
“…This approach has been implemented both using a hand-guided, optically tracked single detector such as is used for radio-guided surgery, 10,11 as well as a robot-mounted mini gamma camera, as a standalone device 12 or in combination with a C-arm computed tomography scanner. 13 These systems have demonstrated that radioactive hot spots, such as small spheres resembling metastatic lymph nodes, can be localized with high precision, delivering image quality close to that of regular SPECT devices. So far these studies restricted themselves to "hot" regions with limited or no background radiation, which is realistic to assume for lymph nodes, localized metastases, or the targeted injection of radioactivity, but not for the thyroid case at hand.…”
Section: Introductionmentioning
confidence: 99%
“…We have recently proposed the acquisition of 325 'desired views' for digital substraction angiography based on simulated X-rays, or digitally reconstructed radiographs (DRR), generated from CT-Angiography [16]. Similar approaches resulted in an automatic acquisition of desired intra-operative 3D and B-mode US views based on pre-operative MRI images [17] as well as the first intra-operative robotic SPECT-CT imaging based on 330 pre-acquired CBCT data [18] (see Fig. 6) Figure 6: Based on pre-interventional diagnostic imaging data such as MRI, intra-operative ultrasound acquisitions can be performed fully automatically without required guidance (left).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Availability of nuclear images in the interventional suite can be achieved by installation of a SPECT/CT scanner in the interventional suite. As an alternative, one could use a mobile or handheld gamma camera . Also, worth mentioning in this context is a mobile hybrid imaging device, combining a conventional c‐arm with gamma cameras, which is currently being developed by our group .…”
Section: Introductionmentioning
confidence: 99%